Penerapan Media Pembelajaran Google Classroom dan Google Meet untuk Meningkatkan Hasil Belajar Ekonomi Siswa Kelas XI IPS 3 SMA Kolese De Britto Yogyakarta (Business and Accounting Education Journal, 2022)
This study aims to analyze the application of google classroom and google meet learning media to improving economic learning outcomes for class XI IPS 3 SMA Kolese De Britto Yogyakarta. This classroom action research population consisted of 28 students in class XI IPS3 as research subjects. The implementation of this classroom action research was carried out in two cycles covering four stages, namely planning, action, observation and reflection. Data collected by observation, questionnaires and documentation. Data were analyzed descriptively. The results of this study indicate that the application of Google Classroom learning media can significantly increase learning outcomes with an average of 7.47% and in cycle 2 the application of Google Classroom and Google Meet media has an average increase of 10.27%.